Hydraulic characteristics of typical bank‐protection works along the Brahmaputra/Jamuna River, Bangladesh. Issue 4 (10th January 2013) - Nakagawa, H.; Zhang, H.; Baba, Y.; Kawaike, K.; Teraguchi, H.
Abstract Severe bank erosion is one of the most challenging problems in the management of large rivers in Bangladesh. This paper describes the detailed flow patterns around typical bank‐protection works on the Brahmaputra/Jamuna River as well as their morphological implications. Based on field surveys at several locations along this large alluvial river that are highly susceptible to erosion, attempts are made to clarify the flow fields and mechanisms of bank erosion. The performance of existing measures such as revetments and spur dykes are evaluated, and possible solutions for further enhancements are proposed. It is found that existing conventional works are generally huge in both size and cost, potentially exerting great disturbances on the river's dynamism and ecosystem. That said, the Bandal – a historied and indigenous structure – is cost‐effective and environmentally friendly. This study suggests the recurrent use of Bandal‐like structures for channel stabilisation and flood management of the braided Brahmaputra/Jamuna River.